KONSERVASI DAN PEMBUATAN KATALOG NASKAH LONTAR DI DESA KLATING TABANAN - ANTARA, NALA; WIJANA, I M.; SUARDIANA, I W. (Buletin Udayana Mengabdi, 2012)
The Balinese written tradition contain of various thing. These indicate how spacious their knowledge to organized their civilization continuity. The facts today, our generations of Balinese written tradition forgotten their perfectly forefather cultural heritage. They were not only leave the lontar script as a civilize forefather stationary also forget their letters use to explicit their thought gradually deserted. The more tragic fact fatally wounded which has no longer time to learn about Balinese culture which has explicit in lontar script on formal education. Beside, lontar script not only collected by formal institutions like Bali Province Government of Cultural, Faculty of Letters Udayana University, etc, but many of these collected personally. In the most serious condition, the personal collectors has not ability to take care the manuscript as far as longer, also they has not ability to confirm how to use the languages and cannot read the Balinese alphabet well. The phenomena above has not enough a good sufficient solution cause the policy in Bali for the perfectly written tradition is not consequence to save these .The Service Program for Society 0f Udayana University is one of a strategic institution to save the original text which is spelled out. Therefore, it’s really needed to give more “energy” to this institution and to those who has really dedicated to save our perfectly forefather cultural heritage from disappears. .